Economic Dominance, the "American Dream, " and Homicide: A Cross‐National Test of Institutional Anomie Theory. Issue 1 (11th November 2014) - Hughes, Lorine A.; Schaible, Lonnie M.; Gibbs, Benjamin R.
<x xml:space="preserve">Abstract</x> This article presents a cross‐national test of Messner and Rosenfeld's (1994) institutional anomie theory. Drawing on multiple data sources, including the United Nations, World Bank, World Values Survey, and Heritage Foundation, we examine relationships between economic dominance, indicators of culture, and homicide among a sample of 50 nations. Additionally, we assess the thesis of "American exceptionalism, " a unique cultural complex implicated by Messner and Rosenfeld as a cause of high rates of serious crime in the United States. Results from OLS regression models provide mixed support for the theory. While none of the theoretical predictors exhibits a statistically significant direct effect on homicide, findings suggest that homicide occurs most often in countries where free‐market principles and practices drive the economy and where core cultural commitments are oriented toward achievement, individualism, fetishism of money, and universalism. However, contrary to expectations, the impact of a market‐driven economy is not more pronounced in countries with weakened non‐economic institutions, and results provide only limited evidence in support of the American exceptionalism thesis. The theoretical implications of these findings are discussed.